Developing a Culturally-Based Pottery Class for Educational Tourism in Bali’s Vocational School - Dewi, Putu Ayu Puri Sintya; Subagia, I Nyoman; Yasa, I Ketut Wardana (Darul Yasin Al Sys, 2025)
This study addresses the underexplored integration of cultural heritage education within vocational tourism programs in Indonesia, focusing on its role in cultural preservation and youth empowerment. It investigates the development dynamics, internal readiness, and stakeholder perceptions of the Pottery Class at the Teaching Factory of SMKN 2 Sukawati as a model of culturally embedded educational tourism. Employing a qualitative design, the research sampled 50 participants, including students, teachers, tourists, and local artisans selected via purposive sampling. Data collection involved semi-structured interviews, participant observation, questionnaires, and document analysis, followed by thematic analysis. Findings indicate that cultural learning motivates 78% of tourists, while the program enhances students’ cultural confidence and entrepreneurial interest. However, challenges persist in marketing, language barriers, and public awareness. These outcomes support experiential learning and cultural tourism theories. The study concludes that the Pottery Class effectively bridges vocational education and cultural tourism, advancing both heritage preservation and economic development objectives. Theoretically, it contributes to understanding school-based tourism models, while practically, it offers recommendations for policymakers, educators, and tourism stakeholders to improve program packaging, forge strategic partnerships, and incorporate digital cultural storytelling. Future research directions include comparative analyses of similar programs in diverse cultural contexts and evaluation of long-term tourist learning outcomes.